Obesity mediated dysregulation in the expression and action of myostatin - Wilhelmsen, Andrew (2022)
Background: Obesity is often associated with impaired sensitivity to the effects of insulin (insulin resistance) and dietary protein (anabolic resistance) and may exacerbate the age-related decline of skeletal muscle (sarcopenia). Myostatin is a protein that negatively regulates skeletal muscle growth but its inhibition in rodents also improves insulin sensitivity. In humans, myostatin appears to be upregulated by obesity and associated with insulin resistance, but observations are confounded by lifestyle factors and ageing. Aims: To delineate between the effects of obesity and ageing on myostatin expression in human skeletal muscle; to investigate the underlying causes of these effects; and to establish the functional significance and interconnectivity of modulating insulin sensitivity and myostatin expression in human skeletal muscle cells. Methods: In Chapter 3 a cross-sectional analysis of skeletal muscle gene expression was undertaken, in conjunction with correlation analyses between serum myostatin and descriptive characteristics, to isolate the effects of obesity and ageing per se on myostatin expression and abundance. In Chapters 4 and 5, in vitro and ex vivo techniques were employed using human primary myotubes to investigate the potential involvement of lipid-induced insulin and anabolic resistance and secretory cross-talk between subcutaneous adipose tissue and muscle, in the obesity-mediated upregulation of myostatin and the associated impairment of insulin and anabolic sensitivity. In Chapter 6, the novel polyphenol metabolite Urolithin A was applied to human myotubes and a model of adipocytes, to investigate its therapeutic potential to enhance insulin and anabolic sensitivity and to suppress myostatin expression. Results: In Chapter 3 it was revealed that muscle myostatin expression is uniquely upregulated by obesity with ageing, but not by ageing in the absence of obesity, and occurs concurrently with insulin resistance and abnormal regulation of pathways involved in the maintenance of skeletal muscle mass. This association was corroborated by positive correlations between serum myostatin and multiple indices of adiposity, but not age. In Chapters 4 and 5 it was demonstrated that neither acutely elevated fatty acid availability (which induced insulin and anabolic resistance), nor chronic exposure to obese subcutaneous adipose tissue conditioned medium (which did not induce insulin or anabolic resistance but altered the expression of genes involved in myogenesis and muscle protein breakdown) recapitulated the obesity-mediated upregulation of myostatin expression. In Chapter 6 it was demonstrated for the first time that Urolithin A suppresses myostatin expression and enhances glucose transport in human myotubes (and 3T3-L1 adipocytes), the latter of which was associated with an upregulation of GLUT4 expression. Conclusions: Skeletal muscle myostatin expression is uniquely upregulated by obesity per se, but this does not appear to be mediated by lipid-induced insulin resistance, nor by the secretory milieux of obese subcutaneous adipose tissue. Nevertheless, both models perturbed factors involved in myogenesis and muscle protein breakdown, independent of an upregulation of myostatin. Thus, the factors responsible for the obesity-mediated upregulation of myostatin remain to be elucidated and future work to establish such causality is required. Furthermore, translational research to investigate the potential of Urolithin A to enhance glucose handling in peripheral tissues and to repress myostatin’s inhibitory effects on muscle growth is warranted in humans and could be of particular benefit in conditions such as sarcopenic obesity.